Relationship Between Nomophobia, Depression, and Anxiety in Adolescents - Behjatipour, Mina; Abdi, Hassan; Pyadeh-Kohsar, Abulqasem (KMAN Counseling & Psychology Nexus, 2026)
The aim of the present study was to investigate the relationship between nomophobia, depression, and anxiety among male adolescents aged 12 to 18 years in high schools of Sabzevar County. In terms of purpose, this study was fundamental research, and in terms of methodology, it employed a descriptive-correlational design. The statistical population included male adolescents aged 12 to 18 years attending high schools in Sabzevar County during the 2023–2024 academic year. According to statistics provided by the Ministry of Education of this city, the population consisted of 1,031 students. A total of 278 participants were selected through non-probability convenience sampling based on the Morgan table. The research instruments included the Nomophobia Questionnaire developed by Yildirim and Correia (2015), the Aaron T. Beck Depression Inventory (1978), and the Aaron T. Beck Anxiety Inventory (1988). Data were analyzed using Pearson correlation coefficient and simultaneous regression analysis. The results indicated that students’ depression and anxiety were predicted by the nomophobia variable (p < .001). Based on the findings, it can be concluded that depression and anxiety may result from changes in the nomophobia variable among male adolescents aged 12 to 18 years in high schools of Sabzevar County.